Pengaruh Literasi Keuangan, Karakteristik Wirausaha, dan Penggunaan Informasi Akuntansi Terhadap Keberhasilan UMKM Industri Tekstil di Kecamatan Klungkung pada Masa Pandemi Covid-19 - I Komang Gede Wirayasa; I Nyoman Putra Yasa (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2023)
Abstract The purposes of this study were to determine the effect of financial literacy, entrepreneurial characteristics, and the use of accounting information on the success of the textile industry MSMEs in Klungkung District during the Covid-19 Pandemic Period. The sample size was determined using the Isaac & Michael formula and obtained as many as 185 textile industry MSMEs with the respondent selection technique using purposive sampling. Sources of data in this study are primary data and secondary data. This study used a quantitative research design with data collection methods carried out by distributing questionnaires. The data analysis method used is a multiple linear regression test. The data were analyzed using SPSS version 23 for windows. The results of this study indicate that: (1) financial literacy has a positive and significant impact on the success of the textile industry MSMEs in Klungkung District during the Covid-19 pandemic; (2) entrepreneurial characteristics have a positive and significant impact on the success of the textile industry MSMEs in Klungkung District during the Covid-19 pandemic; and (3) the use of accounting information has a positive and significant effect on the success of the textile industry MSMEs in Klungkung District during the Covid-19 pandemic. Keywords : The success of the textile industry MSME, financial literacy, entrepreneurial characteristics, accounting information.